The co-decision trap: How the co-decision procedure hindered CAP reform - Marko Lovec; Emil Erjavec (Intereconomics, 2015)
Since the 1980s, the European Union's Common Agricultural Policy has undergone a series of reforms that were facilitated by the changes in decision-making rules such as the introduction of the qualified majority vote. This article argues that the introduction of the co-decision procedure under the Lisbon Treaty, which increased the European Parliament's legislative powers, has generated a 'co-decision trap' that has hindered further reforms.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Politische Entscheidung; Politisches System; EU-Staaten